EVALUASI STRUKTUR JEMBATAN GANTUNG UNTUK PEJALAN KAKI DI KECAMATAN SIMPANG GAMBIR KAB. MANDAILING NATAL - , ALI WARDANA HASIBUAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The bridge is one of the most important buildings in the smooth ground transportation. Construction of a suspension bridge is one method that is very precise in addressing problems in land transport span rivers or valleys because of the very wide, very difficult to build a pillar in the middle of streams and steep valleys, implementation time, and cost issues. Suspension bridge for pedestrian in simpang gambir district mandailing natal regency need in the evaluation to determine the strength of the structure. The method used in the evaluation of the structure of a suspension bridge for pedestrian simpang gambir subdistrict input mandailing natal regency with the planning image data into the SAP program in 2000. Suspension bridge for pedestrian simpang gambir district mandailing natal regency profile analysis showed mostly very wasteful in view of the elevation colors SAP safety structure in the program in 2000.